Is it reasonable to shorten the length of cemented stems? A finite element analysis and biomechanical experiment - Li, Junyan; Xiong, Liang; Lei, Chao; Wu, Xinyu; Mao, Xinzhan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Uncemented short stems have been shown to optimize load distribution on the proximal femur, reducing stress shielding and preserving bone mass. However, they may adversely affect the initial stability of the stems. To date, most research conducted on short stems has predominantly centered on uncemented stems, leaving a notable dearth of investigations encompassing cemented stems. Therefore, this study aimed to investigate the length of cemented stems on the transmission of femoral load patterns and assess the initial stability of cemented short stems. Method: A series of finite element models were created by gradient truncation on identical cemented stem. The impact of varying lengths of the cemented stem on both the peak stress of the femur and the stress distribution in the proximal femur (specifically Gruen zones 1 and 7) were assessed. In addition, an experimental biomechanical model for cemented short stem was established, and the initial stability was measured by evaluating the axial irreversible displacement of the stem relative to the cement. Result: The maximum von-Mises stress of the femur was 58.170 MPa. Spearman correlation analysis on the shortened length and von-Mises stress of all nodes in each region showed that the p-values for all regions were less than 0.0001, and the correlation coefficients (r) for each region were 0.092 (Gruen Zone 1) and 0.366 (Gruen Zone 7). The result of the biomechanical experiment showed that the irreversible axial displacement of the stem relative to cement was −870 μm (SD 430 μm). Conclusion: Reducing the length of a cemented stem can effectively enhance the proximal load of the femur without posing additional fracture risk. Moreover, the biomechanical experiment demonstrated favorable initial stabilities of cemented short stems.